Confined space synthesis of fully alloyed and sinter-resistant AuPd nanoparticles encapsulated in porous silica - Samanta, Anupam; Rajesh, Thattarathody; Devi, R. Nandini (Journal of Materials Chemistry A, 2014)
Facile synthesis of highly sinter-resistant silica encapsulated Au-Pd alloy nanocatalysts with average particle size stabilized at similar to 4.5 nm even after calcination at 750 degrees C temperature is reported. The synthesis was achieved by utilizing thiol protected ultra small clusters of Au and Pd as precursors for silica encapsulation. The presence of intimate mixtures of the clusters within silica encapsulation ensures the formation of fully alloyed nanoparticles at high temperatures, at the same time controlling further growth and sintering. At optimum alloy compositions, these catalysts showed high catalytic activity for CO oxidation displaying low light-off temperatures.

Co-Ni layered double hydroxide for the electrocatalytic oxidation of organic molecules: an approach to lowering the overall cell voltage for the water splitting process - Shilpa, Nagaraju; Pandikassala, Ajmal; Krishnaraj, Perayil; Walko, Priyanka S.; Devi, R. Nandini; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2022)
Electrocatalytic oxidation of simple organic molecules oilers a promising strategy to combat the sluggish kinetics of the water oxidation reaction (WOR). The low potential requirement, inhibition of the crossover of gases, and formation of value-added products at the anode are benefits of the electrocatalytic oxidation of organic molecules. Herein, we developed cobalt-nickel-based layered double hydroxide (LDH) as a robust material for the electrocatalytic oxidation of alcohols and urea at the anode, replacing the WOR. A facile synthesis protocol to form LDHs with different ratios of Co and Ni is adapted. It demonstrates that the reactants could be efficiently oxidized to concomitant chemical products at the anode. The half-cell study shows an onset potential of 1.30 V for benzyl alcohol oxidation reaction (BAOR), 1.36 V for glycerol oxidation reaction (GOR), 1.33 V for ethanol oxidation reaction (EOR), and 1.32 V for urea oxidation reaction (UOR) compared with 1.53 V for WOR. Notably, the hybrid electrolyzer in a full-cell configuration significantly reduces the overall cell voltage at a 20 mA cm(-2) current density by similar to 15% while coupling with the BAOR, EOR, and GOR and similar to 12% with the UOR as the anodic half-cell reaction. Furthermore, the efficiency of hydrogen generation remains unhampered with the types of oxidation reactions (alcohols and urea) occurring at the anode. This work demonstrates the prospects of lowering the overall cell voltage in the case of a water electrolyzer by integrating the hydrogen evolution reaction with suitable organic molecule oxidation.
Keywords: electrocatalytic oxidation; energy conversion; imidazole mediated; Layered compounds; water splitting

Cobalt-manganese modified theophrastite phase of nickel hydroxide nanoflower arrays on nickel foam as a self-standing bifunctional electrode for overall water electrolysis - Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Barik, Sidharth; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2023)
Designing and developing self-supported electrodes for water electrolysis is attractive as compared to conventional catalyst-coated electrodes. Herein, a (Co0.3Mn0.1Ni0.6)(OH)(2)/NF nanocomposite is prepared by anchoring (Co0.3Mn0.1Ni0.6)(OH)(2)via simple one-pot hydrothermal synthesis on nickel foam. The presence of Mn induces the external electronic structure of Co(OH)(2), and this also improves the electrochemically active surface area (ECSA). These favor better accessibility of active sites and increased intrinsic activity for the OER and HER. (Co0.3Mn0.1Ni0.6)(OH)(2)/NF has shown promising electrochemical activity toward the OER and HER in a 1 M KOH electrolyte, with an overpotential of 270 mV for the OER and 163 mV for the HER to deliver 10 mA cm(-2) current density. The overall water splitting was performed by employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as both the cathode and anode by displaying a voltage of 1.62 V at 10 mA cm(-2), which is comparable to that extracted from a similar system based on the state-of-the-art Pt/C@NF cathode and RuO2@NF anode (1.60 V at 10 mA cm(-2)) standard electrode pair. Interestingly, at high current densities, the (Co0.3Mn0.1Ni0.6)(OH)(2)/NF//(Co0.3Mn0.1Ni0.6)(OH)(2)/NF system displayed better overall water splitting performance (1.78 V at 100 mA cm(-2)) compared to its Pt/C@NF//RuO2@NF (1.89 V at 100 mA cm(-2)) counterpart while displaying a stable output during the evolution period that lasted for 24 h. The amounts of H-2 and O-2 produced are estimated to be 701.2 and 358.6 mmol, respectively, at a time interval of 1 h; these amounts correspond to an similar to 1 : 2 ratio of O-2 and H-2, respectively. This study confirms the capability for employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as a bi-functional and self-standing electrode for the realistic demonstrations of overall water splitting applications.

Continuous flow synthesis of mesoporous silica particles with tunable size and structure - Jundale, Rajashri B.; Prasad, Bhagavatula L. V.; Devi, R. Nandini; Kulkarni, Amol A. (Industrial and Engineering Chemistry Research, 2024)
We have developed a continuous process to prepare mesoporous silica particles of different sizes and narrow size distribution in a tubular reactor. The method is based on the use of well-known Stober synthesis in the presence of cationic surfactant in methanol-water solvent system and trimethylbenzene as pore swelling agent to form porous silica particles. We observed that reaction parameters had enormous effects on particle size, distribution, and numerous morphological aspects. We demonstrated that these properties may be modified by adjusting the reaction temperature, base concentration, and surfactant concentration. MSPs of spherical morphology with variable size from 400 to 1000 nm produced with the surface area >600 m(2)/g and pore diameter of 2-4 nm. Large scale production is demonstrated by increasing reactor volume using 1/4 in. PTFE tubing from 20 to 163 mL, with this production of MSPs increased from 0.35 to 3 g/h. The method has been extended for high yield production at the kilogram scale using this approach, which will pave the way toward the industrialization of mesoporous silica based materials.

Coke management: unveiling the role of Ce substitution in Gd2Zr1.8Ni0.2O7-δ catalyst for dry reforming of methane - Ghodke, Seema R.; Mule, Harshada M.; Bhatkar, Akash; Devi, R. Nandini (Energy & Fuels, 2025)
The redox characteristics of cerium have become crucial elements in the carbon gasification process during methane dry reforming. This work examines the effect of cerium substitution in the Gd2Zr1.8Ni0.2O7-delta catalyst during methane dry reforming, employing a range of Ce-substituted Gd2Zr1.8-x Ni0.2Ce x O7-delta (x = 0.1, 0.2, 0.5, 0.75) catalysts synthesized via the citrate gel method. The materials crystallized in a fluorite structure, as verified by X-ray diffraction analysis and Raman spectroscopy. Enhanced reducibility of the substituted catalysts was assessed through H2-temperature-programmed reduction analysis. CO2 and O2 desorption studies along with X-ray photoelectron spectroscopy validated the enhanced basicity and generation of active oxygen and hydroxyl species. The enhanced activity and coke gasification in Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst are attributed to surface hydroxyl species, and prominent intermediate carbonate and bicarbonate species were further verified by in situ infrared spectroscopy. The high basicity of the Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst and high concentrations of oxygen vacancies (similar to 66.4%) enhances CO2 adsorption and desorption, resulting in continuous CO2 activation, leading to less carbon formation and superior activity of the catalyst. The Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst exhibits the highest CH4 and CO2 conversion rates, at 85% and 93.5%, respectively, and remains stable for 100 h. Postreaction analysis of Gd2Zr1.6Ni0.2Ce0.2O7-delta confirms structure stability and less carbon formation compared to other substituted catalysts in dry reforming of methane. This study demonstrates that the moderate concentration of Ce in the Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst exhibits balanced activity and coke gasification capacity in the dry reforming of methane for a longer duration.

Continuous flow hydrodeoxygenation of lignin-derived guaiacol to cyclohexanol over durable Al2O3 hollow fiber supported co catalyst - Singh, Dheerendra; Jogdand, Shunottara M.; Devi, R. Nandini; Dhepe, Paresh L. (ChemCatChem, 2025)
The drive to decarbonize the chemical, oil, and gas industries through use of bio-derived resources is intensifying. This study focuses on converting lignin-derived phenolic compounds into cyclohexanol, a precursor for adipic acid production. The alumina hollow fiber supported cobalt catalyst (5Co/AHF@capillary) prepared by capillary action method was found to consist cobalt in both metallic and +delta oxidation states. Initial tests in a batch-mode reactor showed promising results, with 5Co/AHF@capillary catalyst demonstrating catalytic activity comparable to Ru/Al2O3 systems (225 degrees C, 1 MPa H-2, 4 h), achieving similar to 86% cyclohexanol yield in guaiacol hydrodeoxygenation reactions. The catalytic system was then adapted for continuous flow reactors under milder conditions (300 degrees C, 2.5 MPa H-2, 18 mL min(-1)), resulting in 83% guaiacol conversion and 74% cyclohexanol yield. The durability of the catalyst was checked for >80 h and results claim that catalyst was active in yielding consistent results. The roles of catalyst preparation method, hydrogen pressure, solvent, WHSV were thoroughly checked and discussed.
Keywords: biomass valorization; Carbon; Co/Al2O3; Cyclohexanol; lignin